2022
DOI: 10.2754/avb202291030243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oestrus synchronization with different lengths of progesterone-impregnated sponges and equine chorionic gonadotropin on reproductive efficiency in Romanov ewes during the non-breeding season

Abstract: This study aimed to determine the effects of different lengths of progesterone and equine chorionic gonadotropin (eCG) treatment on reproductive performance during the non-breeding season in ewes. Progesterone-impregnated sponges were inserted intravaginally for 7 d in Group 1 (G1, n = 24), 9 d in Group 2 (G2, n = 25), and 11 d in Group 3 (G3, n = 24). On the day of sponge removal, eCG (350 IU) was injected and 24 h later the ewes were exposed to rams. Pregnancy was diagnosed by transrectal ultrasonography 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, in small ruminants, achieving pregnancy and lamb production during the non-breeding season can lead to additional economic benefits. In sheep, eCG plays a vital role in inducing estrus and follicular development outside of the breeding season (1,4,15,17). In our study, the use of eCG with progesterone-containing sponges during the non-breeding season in Anatolian Merino sheep resulted in excellent estrus induction, and this success was reflected in other fertility parameters, such as pregnancy rates.…”
Section: Resultsmentioning
confidence: 60%
“…However, in small ruminants, achieving pregnancy and lamb production during the non-breeding season can lead to additional economic benefits. In sheep, eCG plays a vital role in inducing estrus and follicular development outside of the breeding season (1,4,15,17). In our study, the use of eCG with progesterone-containing sponges during the non-breeding season in Anatolian Merino sheep resulted in excellent estrus induction, and this success was reflected in other fertility parameters, such as pregnancy rates.…”
Section: Resultsmentioning
confidence: 60%
“…In this study, all ewes in short‐term group came into estrus and short‐term group had the highest fertility rate (Eldomany et al, 2023). In the study of Kuru et al (2022), the effect of different lengths of progesterone treatment on reproductive performance of ewe during the non‐breeding season was investigated. The estrus response, pregnancy rate, lambing rates, litter sizes and multiple birth rate were excellent for short‐term progesterone treatment; they suggested it as an alternative to long‐term methods (Kuru et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Kuru et al (2022), the effect of different lengths of progesterone treatment on reproductive performance of ewe during the non-breeding season was investigated. The estrus response, pregnancy rate, lambing rates, litter sizes and multiple birth rate were excellent for short-term progesterone treatment; they suggested it as an alternative to long-term methods (Kuru et al, 2022). Several studies have shown that estradiol is a good marker of follicular function for both sheep and cattle, and healthy antral follicles contain high estradiol concentrations (Campbell et al, 1995;Ireland & Roche, 1983).…”
Section: Ta B L Ementioning
confidence: 99%